2019
DOI: 10.3390/app9235199
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Skin Friction Drag Reduction in the Turbulent Boundary Layer Using Riblets

Abstract: A unique approach to evaluate the reduction of skin friction drag by riblets was applied to boundary layer profiles measured in wind tunnel experiments. The proposed approach emphasized the turbulent scales based on hot-wire anemometry data obtained at a sampling frequency of 20 kHz in the turbulent boundary layer to evaluate the skin friction drag reduction. Three-dimensional riblet surfaces were fabricated using aviation paint and were applied to a flat-plate model surface. The turbulent statistics, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…The size parameter of the circular concave structure was considered: diameter D, the lateral distance W, the longitudinal distance L, and the depth S. To facilitate the design and arrangement, the depth S of the circular concave structure is half of the circular concave diameter D. The size design of the circular concave structure is shown specifically in Figure 5. The value range of D, W, L and S is given as [10,50], [60, 160], [60, 160], [5,25] respectively; its numeric type is integer and unit is mm. According to many bionics experiments, the soil animal, the dung beetle, can move freely in the soil due to the circular concave shape of its non-smooth surface and the arrangement of its circular concave structure.…”
Section: Size Design and Arrangement Of Circular Concave Structurementioning
confidence: 99%
See 1 more Smart Citation
“…The size parameter of the circular concave structure was considered: diameter D, the lateral distance W, the longitudinal distance L, and the depth S. To facilitate the design and arrangement, the depth S of the circular concave structure is half of the circular concave diameter D. The size design of the circular concave structure is shown specifically in Figure 5. The value range of D, W, L and S is given as [10,50], [60, 160], [60, 160], [5,25] respectively; its numeric type is integer and unit is mm. According to many bionics experiments, the soil animal, the dung beetle, can move freely in the soil due to the circular concave shape of its non-smooth surface and the arrangement of its circular concave structure.…”
Section: Size Design and Arrangement Of Circular Concave Structurementioning
confidence: 99%
“…The drag reduction research on non-smooth surface structures has received a great deal of attention [4][5][6]. Drag force can be divided into two different types, that is, pressure drag and friction drag.…”
Section: Introductionmentioning
confidence: 99%
“…Here, τ designates the time lag at which the correlation is measured. Since the duration of the sampling has to be finite, the integration is limited to a time lag, τ 0 , for which the absolute value of the auto-correlation coefficient becomes less than 0.0005 and its gradient becomes less than 0.005, i.e., R pp < 0.0005 and dR p p dτ < 0.005 [44].…”
Section: Auto-correlations Of Unsteady Surface Pressurementioning
confidence: 99%
“…Turbulent skin friction drag reduction with longitudinal microgrooves and riblets in channel flow is analyzed using lattice Boltzmann method by Rastegary and Akhavan (2018). Turbulent boundary layer characteristics for a flat plate model with riblet surface is examined in wind tunnel experiments by Takahashi et al (2018). The results revealed that skin friction drag is reduced aboaut 3.6% at free stream velocity of 42m/s.…”
Section: Nomenclaturementioning
confidence: 99%